The Importance of The Family in Preventing and Applying Child Safety in Islamic Way in The Makassar City - Muhasidah, Muhasidah; Abu, Saddiah; Nasrullah, Nasrullah (International Conference of Moslem Society, 2018)
The Preliminary study conducted through observation and interviews with 10 parents in the city of Makassar found 6 out of 10 children aged under five suffered accidents due to falling, exposed to hot water, choking on food because of eating alone, electrocution, cheek wounds due to puncture meatballs, and 1 person with 9 months old died in March 2013. Allah has written in the Book of the Qur'an about the prayers of the Prophets, who ask for protection on their children. As for the Word of God with the meaning that prays to your Lord with humility and a gentle voice, prayer is a weapon for believers, prayer can change a person's destiny if the prayer is accepted by God. This research use descriptive analytic design with cross sectional approach. The number of samples in the study were 62 families with children aged 6 months to 6 years. Univariate analysis to see the description of frequency and percentage level of knowledge and attitude of the family about an implementation of child safety with Islamic way, and bivariate analysis to know relationship between knowledge and attitude of family with applying child safety in accordance with Islamic way, using Chi statistical test -Square with Î± = 0.05.The results showed that there is a significant relationship between knowledge and attitude of the family with the implementation of child safety according to Islamic law, to prevent and handle child safety in the family in Makassar city.